Novel Selective IDO1 Inhibitors with Isoxazolo[5,4-d]pyrimidin-4(5H)-one Scaffold - Ana Dolšak; Tomaž Bratkovič; Larisa Mlinarič; Eva Ogorevc; Urban Švajger; Stanislav Gobec; Matej Sova (MDPI AG, 2021)
Indoleamine 2,3-dioxygenase 1 (IDO1) is a promising target in immunomodulation of several pathological conditions, especially cancers. Here we present the synthesis of a series of IDO1 inhibitors with the novel isoxazolo[5,4-d]pyrimidin-4(5H)-one scaffold. A focused library was prepared using a 6- or 7-step synthetic procedure to allow a systematic investigation of the structure-activity relationships of the described scaffold. Chemistry-driven modifications lead us to the discovery of our best-in-class inhibitors possessing p-trifluoromethyl (23), p-cyclohexyl (32), or p-methoxycarbonyl (20, 39) substituted aniline moieties with IC50 values in the low micromolar range. In addition to hIDO1, compounds were tested for their inhibition of indoleamine 2,3-dioxygenase 2 and tryptophan dioxygenase, and found to be selective for hIDO1. Our results thus demonstrate a successful study on IDO1-selective isoxazolo[5,4-d]pyrimidin-4(5H)-one inhibitors, defining promising chemical probes with a novel scaffold for further development of potent small-molecule immunomodulators.